From Entry to Early Dissemination—Toxoplasma gondii's Initial Encounter With Its Host - Delgado Betancourt, Estefania; Hamid, Benjamin; Fabian, Benedikt T.; Klotz, Christian; Hartmann, Susanne; Seeber, Frank (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is a zoonotic intracellular parasite, able to infect any warm-blooded animal via ingestion of infective stages, either contained in tissue cysts or oocysts released into the environment. While immune responses during infection are well studied, there is still limited knowledge about the very early infection events in the gut tissue after infection via the oral route. Here we briefly discuss differences in host-specific responses following infection with oocyst-derived sporozoites versus tissue cyst-derived bradyzoites. A focus is given to innate intestinal defense mechanisms and early immune cell events that precede T. gondii’s dissemination in the host. We propose stem cell-derived intestinal organoids as a model to study early events of natural host-pathogen interaction. These offer several advantages such as live cell imaging and transcriptomic profiling of the earliest invasion processes. We additionally highlight the necessity of an appropriate large animal model reflecting human infection more closely than conventional infection models, to study the roles of dendritic cells and macrophages during early infection.